Utility of VerifyNow to assess the immediate pharmacodynamic response of chewed and swallowed aspirin: comparison with aggregometry - Kevin P. Bliden; Parshotam Kundan; Danielle Kraft; Rueshil Parekh; Sahib Singh; Aravind D. Babu; Anika P. Shah; Udaya S. Tantry; Paul A. Gurbel (Platelets)
VerifyNow (VN) test is a less laborious method to assess pharmacodynamics (PD) compared to light transmittance aggregometry (LTA). VN assay has not been used to study the immediate PD effects of acetylsalicylic acid (ASA). Ten healthy volunteers were randomly assigned to a single 162 or 650 mg dose of chewed and swallowed ASA. Pharmacodynamic and pharmacokinetic measurements were performed at baseline and serially up to 60 min after ASA administration. Onset by VN was 20 ± 7 min with 162 mg and 13 ± 7 min with 650 mg ASA (p = .07). Onset by 1 mM AA-induced PA was 13 ± 12 min with 162 mg and 7 ± 3 min with 650 mg ASA (p=NS). VN correlated with AA-induced PA (r = 0.80, p < .001) and serum TxB2 levels (r = 0.76, p < .001). 95% inhibition of serum TxB2 was achieved at 38 ± 22 min and 22 ± 8 min with the 162 and 650 mg ASA, respectively (p = .08). The onset and extent of the antiplatelet effect of 650 mg ASA is numerically faster and greater than the 162 mg dose. VN identifies the onset, extent, and dose response to ASA therapy. The ease of using VN should facilitate multicenter PD investigations of ASA.